The effect of Islamic microfinance services on micro-entrepreneurs’ performance in Southern Thailand - Ruslee Nuh (2019)
The research on Islamic microfinance towards micro-entrepreneurs’ performance is still scanty in Thailand. To investigate this issue, this study attempts to examine the effect of Islamic microfinance (credit, savings, and training) on micro-entrepreneurs’ performance (i.e. economic and social performance) in Thailand. This study further examines the moderation effect of internal control (bank monitoring) and entrepreneurial self-efficacy towards the relationship between Islamic microfinance and micro- entrepreneurs’ performance. A total of 480 micro-entrepreneurs participated in the survey through a self-administered questionnaire. However, after data screening, only 400 respondents from the survey were used for the data analysis in this study. The main statistical technique used in this study is Structural Equation Modeling (SEM) by using Analysis of Moment Structure (AMOS) version 23. This study has found that all factors of Islamic microfinance (i.e. credit, savings, and training) offered by Islamic microfinance programme under Islamic bank of Thailand bring significant positive effect on the economic and social performance of micro-entrepreneurs in three provinces of Southern Thailand. With regards to the moderation effect, this study has revealed that the moderation effect of both internal controls through bank monitoring and entrepreneurial self-efficacy are significantly moderated in the relationship between Islamic microfinance and micro-entrepreneurs’ performance. Based on the findings, this study can support and give the theoretical contribution to Model of Entrepreneurship Process (Shane, 2003). The findings contribute to the policy makers, Islamic microfinance Institutions and other relevant stakeholders by promoting appropriate microfinance services (credit, savings and training) as well as strictly monitoring and supporting self-efficacy towards micro entrepreneurs to develop micro entrepreneurs in three provinces of Southern Thailand.